2
$\begingroup$

Well, I was doing a problem on recurrence relation , where there was given a an recurrence relation and we had to find $a_{n}$ or simplify the recurrence.

The recurrence relation was $$\begin{align} a_{n} &= \frac{1}{16}(1 + 4a_{n+1} + \sqrt{1+24a_{n+1}} ) \\ a_{0} &= 1 \end{align}$$

What I tried was I reached the equation $$4a_{n} - a_{n+1} = \frac{1+\sqrt{1+24a_{n+1}}}{4} $$ Using formula for quadratic roots and putting $$4a_{n} - a_{n+1} = x = \frac{1+\sqrt{1+24a_{n+1}}}{4}$$ $$\implies Ax^2 + Bx + C = 0$$ $$ A = 2, B = -1, C = -3a_{n+1}$$ And then putting the value of $x$ I tried to solve it but nothing fruitful was obtained.

Edit: I made a mistake in the recurrence relation and now $n$ has been swapped by $n+1$

$\endgroup$
3
$\begingroup$

Hint:

Denote $b_n=\sqrt{1+24a_{n}}$. Then you get $$ 4b_n^2-4=b_{n+1}^2+6b_{n+1}+5, $$ whence $$ 2b_n=\pm (b_{n+1}+3). $$

$\endgroup$
  • $\begingroup$ Thank You. That indeed solved the problem as now we can see $$b_{n+1} = 2b_{n} - 3$$ and thus we get $$b_{n} = 2^{n+1} + 3$$ and putting value of $b_{n}$ we can get $a_{n}$ $\endgroup$ – Mod May 27 '13 at 13:24
  • $\begingroup$ @Mod: OK, you are welcom! $\endgroup$ – Boris Novikov May 27 '13 at 14:18

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.